2022
DOI: 10.1017/s0033291722002616
|View full text |Cite
|
Sign up to set email alerts
|

Treating postpartum insomnia: a three arm randomised controlled trial of cognitive behavioural therapy and light dark therapy

Abstract: Background Insomnia symptoms are common during the postpartum period, yet interventions remain scarce. This trial aimed to simultaneously examine the efficacy of cognitive behavioural therapy (CBT) and light dark therapy (LDT), targeting different mechanisms, against treatment-as-usual (TAU), in reducing maternal postpartum insomnia symptoms. Methods This three-arm randomised controlled trial recruited from the general community in Australia. Nulliparous females 4–12 months postpartum wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The average age of participants in each study ranged from 24 to 34 years. The light equipment for the two trials were light glasses and light visors, respectively (Lee et al., 2013 ; Verma et al., 2022 ), and the rest used light boxes. The intensity of light therapy ranges from 1250 to 10,000 lx, and all studies had morning treatment sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of participants in each study ranged from 24 to 34 years. The light equipment for the two trials were light glasses and light visors, respectively (Lee et al., 2013 ; Verma et al., 2022 ), and the rest used light boxes. The intensity of light therapy ranges from 1250 to 10,000 lx, and all studies had morning treatment sessions.…”
Section: Resultsmentioning
confidence: 99%
“…The daily treatment duration ranged from 30 to 60 min, and the duration of treatment varied between 3 and 6 weeks. All trial controls were <1000 lx dim light, except for one study that used the usual treatment as a control (Verma et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that 12 weeks of pilates training improved the sleep quality of postpartum women. Although there is only one study in the literature on the effect of pilates exercises on postpartum sleep quality (26), methods such as cognitive behavioral therapy and light-dark therapy were found to be effective in reducing sleep problems (43).…”
Section: Resultsmentioning
confidence: 99%
“…The sleep problem seen during the new motherhood period is one of the critical problems that may affect the mother-baby and mother-family harmony that can be seen in the mother (44). In the literature, methods such as cognitive behavioral therapy and Light dark therapy have been used and found effective to reduce sleep problems (43). The improvement in sleep quality, after sleep quality measurement results were compared (F=31,865; p<0.001, ηp2=0.375).…”
Section: Resultsmentioning
confidence: 99%
“…Napping was restricted in studies of individuals with alcohol use disorder (Arnedt et al, 2011), breast cancer (Quesnel et al, 2003), comorbid depression (Wagley et al, 2013), and other psychiatric disorders (Crönlein et al, 2014(Crönlein et al, , 2019(Crönlein et al, , 2020. Strategic napping was recommended for shift workers (Järnefelt et al, 2020) and during perinatal periods (Bei et al, 2023;Manber et al, 2019Manber et al, , 2023Verma et al, 2022) when experiencing significant sleep debt or waking sleepiness. Review of psychiatric medications and adjusting their timing has also been used to reduce daytime sleepiness and subsequently minimise napping (Chiu et al, 2018;Waite et al, 2016).…”
Section: Sleep Hygienementioning
confidence: 99%